1999
DOI: 10.1038/13024
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cAMP-dependent kinase and MAP kinase through a protein tyrosine phosphatase

Abstract: The haematopoietic protein tyrosine phosphatase (HePTP) is a negative regulator of the MAP kinases Erk1, Erk2 and p38. HePTP binds to these kinases through a kinase-interaction motif (KIM) in its non-catalytic amino terminus and inactivates them by dephosphorylating the critical phosphorylated tyrosine residue in their activation loop. Here we show that cyclic-AMP-dependent protein kinase (PKA) phosphorylates serine residue 23 in the KIM of HePTP in vitro and in intact cells. This modification reduces binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
202
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 45 publications
3
202
0
2
Order By: Relevance
“…Saxena et al 21 demonstrated in Jurkat cells that blocking the interaction of HePTP with ERK1/2 by phosphorylating the PKA consensus site within the KIM of HePTP resulted in significant ERK1/2 activation. In contrast to this, we did not observe significantly increased ERK2 activity in K562 cells in which HePTP levels are downregulated as a result of antisense expression (Figures 2a and 3a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saxena et al 21 demonstrated in Jurkat cells that blocking the interaction of HePTP with ERK1/2 by phosphorylating the PKA consensus site within the KIM of HePTP resulted in significant ERK1/2 activation. In contrast to this, we did not observe significantly increased ERK2 activity in K562 cells in which HePTP levels are downregulated as a result of antisense expression (Figures 2a and 3a).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that phosphorylation of this site in PTP-SL and HePTP in response to PKA activation inhibits the interaction of these phosphatases with their substrates and, consequently, results in increased ERK activity. 21,22 In addition, HePTP can be phosphorylated within the N-terminus by activated ERKs and it was suggested that phosphorylation of these sites also interferes with the binding of HePTP to its substrates. 11 Therefore it was proposed that HePTP is involved in suppression of basal ERK activity in the absence of ERK activating signals.…”
Section: Introductionmentioning
confidence: 99%
“…This would couple ERK retention in the nucleus to de-activation, and also prevent this pool of ERK from being re-activated by MEK in the cytosol. Interestingly, the protein tyrosine phosphatases PTP-SL and HePTP have also recently been shown to serve as cytosolic anchors for ERK-1\2 [158,159]. Since they can dephosphorylate ERK-1\2, they ensure that ERKs bound to them are maintained in the inactive state.…”
Section: Where To Go : Erk Anchoring Proteinsmentioning
confidence: 99%
“…cAMP has long been viewed as an inhibitory signal towards mitogenic stimuli by antagonizing the MAP kinase pathway, as illustrated by Rat-1 ®broblast response to EGF (Wu et al, 1993) and to LPA (Cook and McCormick, 1993). Conversely, ERK activation by cAMP and/or PKA has mainly been evidenced by rare examples of transformed cell lines such as cAMPtreated Jurkat cells (Saxena et al, 1999), PC12 neuronal cells (Vossler et al, 1997), a-MSH-stimulated B16 melanoma cells (Busca et al, 2000), and isoproterenol-stimulated HEK293 cells . These cell models have certainly broadened our current knowledge of signalling mechanisms.…”
Section: Introductionmentioning
confidence: 99%